Cost Effectiveness Analysis of Rivaroxaban Compared to Warfarin and Aspirin for Stroke Prevention Atrial Fibrillation (SPAF) in the Indonesian healthcare setting - Dwiprahasto, Iwan; Kristin, Erna; Endarti, Dwi; Pinzon, Rizaldy Taslim; Yasmina, Alfi; Thobari, Jarir At; Pratiwi, Woro Rukmi; Kartika, Yolanda Dyah; Trijayanti, Christiana (Indonesian Journal of Pharmacy, 2019)
Main drugs used in the prevention of stroke among atrial fibrillation (AF) patients are antiplatelets (aspirin) and oral anticoagulants (OAC). OAC therapy can be difficult to administer due to drug and food interactions, adds the burden of required blood monitoring, narrow therapeutic window, and requirements for dose titration. Rivaroxaban is a single-dose oral anticoagulant which does not require blood monitoring, dose titration or has dietary interactions. Phase III clinical data from the ROCKET trial have recently been reported the non-inferiority of rivaroxaban over warfarin for the prevention of strokes in AF patients. To develop an economic model evaluating the clinical and cost-effectiveness of rivaroxaban for the prevention of stroke in non-valvular AF patients in the Indonesian health care settings. We conducted cost effectiveness analysis from the perspective of payer (national health insurance). Effectiveness data used the international data from previous RCT and network metaanalysis studies. Costs data used local data of Indonesia from national health insurance’s reimbursement tariffs. Markov model was used, comprised of health and treatment states describing the management and consequences of AF. The main analysis was based on data from the phase III trials. Three months was used as cycle length. The time horizon was set at patients’ lifetime (20 years). Costs and outcomes were discounted at a 3% annual rate. Subgroup analysis and extensive sensitivity analysis was conducted. Willingness to pay (WTP) threshold in Indonesia was set as 3 times GDP of Indonesia in 2015, equal about IDR 133,375,000 per quality-adjusted life year (QALY). Base case rivaroxaban vs warfarin has ICER of IDR 141,835,063per QALY at the current cost of rivaroxaban IDR 23,500 and ICER of 130,214,687 per QALY at the proposed cost of rivaroxaban IDR 22,000. One-way sensitivity analysis showed that the key drivers of cost-effectiveness were the utility decrement applied to stable warfarin patients, discontinuation/subsequent discontinuation rates for rivaroxaban, and discontinuation/subsequent discontinuation rates for warfarin. The probabilistic sensitivity analysis suggested that rivaroxaban was cost-effective compared to warfarin in about 45% of cases at the WTP per QALY. Rivaroxaban with the proposed price of IDR 22,000 was considered to be more cost-effective when compared to warfarin.